Relationship Between Knowledge And Family Support On Hypertension Medication In Simpang Tanah Lapang Village Community: Relationship Between Knowledge And Family Support On Hypertension Medication In Simpang Tanah Lapang Village Community - Sari, Ika; Rulia Meilina (Jurnal Serambi Ilmu, 2025)
Hypertension is a disease characterized by increased blood pressure above normal limits and is most often suffered by the elderly. Treatment that can be done for hypertension sufferers is to comply with taking hypertension medication, and it is very difficult to do so that family support is needed in carrying it out. This study aims to determine the significant relationship between family support and compliance in taking hypertension medication in the elderly in Kuantan Hilir District. This study was conducted using an analytical observational method along with a cross-sectional research model. The results of this study showed that patients with a good family support category were 46 people (82.1%) and non-compliant in taking hypertension medication with a total of 10 people (17.9%). There is a significant relationship between family support and compliance in taking hypertension medication in the elderly in Kuantan Hilir District. The higher the family support given, the more compliant the patient is in taking hypertension medication.